Au Norm Import in the European Promotion of Regional Integration in Africa - Arfsten, Antonia (Department of Political Studies, 2020)
The relation between the African Union (AU) and the European Union (EU) is the most institutionalised interregional relationship in the world. The EU, being a crucial external agent in African regional integration, exports open regionalism as a political norm through different mechanisms to the AU. Based on a qualitative research design with a constructivist theoretical viewpoint that regards regional organisations as interdependent political authorities, the dissertation examines the AU's receptivity to the EU's attempted norm diffusion and explores genuine AU norm import of European promoted regional integration. A document analysis of official EU and AU declarations and legislation in combination with primary data collected via semi-structured interviews with officials at the United Nations Economic Commission for Africa offers further insights into the African perspective on regional integration. Out of a variety of EU norm export channels, the study identifies capacity-building in the form of technical and financial assistance as most influential in promoting African regional integration processes. While coercion and political dialogue respectively lead to AU resistance and decoupling alias theatre regionalism, capacity-building and positive conditionality result in institutional incorporation and policy changes. A choice-oriented approach traces this genuine norm import in response to civilian norm diffusion mechanisms back to the external agency of the EU, despite major constraints like the United Kingdom's withdrawal from the EU and alternative interregional options within the alliance of emerging market economies. Yet, the limited traceable AU institutional and policy reforms reveal the agency of the AU. Norm import cannot be taken for granted; it only occurs when sufficient incentives are offered to the receiving side. Political dialogue is inspirational, but needs to be supplemented with financial and technical assistance to yield genuine norm import. These findings contribute to a better understanding of prospective EU-AU relations and can be used by policy-makers to adjust interregional negotiations like the on-going post-Cotonou consultations.